’Weisheit, Wahrheit und Witz’: Über die Personalisierung eines Allgemeinguts - Hofmann, Jeanette (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2002)
This paper looks at the history of the individualization of knowledge. Intellectual property is based on the assumption that individuals are originators of insights and ideas. The notion of the author as creator is a recent invention. Until late 18th century, literati were regarded as craftsmen or mediators, who merely write down the divine wisdom by following the rules of rhetoric. The author as defined in modern copyright law thus gets a lot of credit for intellectual achievements that once were believed to be public domain.